Targeting Nutrient Dependency in Cancer Treatment - Fan, Kexin; Liu, Zhan; Gao, Min; Tu, Kangsheng; Xu, Qiuran; Zhang, Yilei (Frontiers in Oncology, 2022)
Metabolic reprogramming is one of the hallmarks of tumor. Growing evidence suggests metabolic changes that support oncogenic progression may cause selective vulnerabilities that can be exploited for cancer treatment. Increasing demands for certain nutrients under genetic determination or environmental challenge enhance dependency of tumor cells on specific nutrient, which could be therapeutically developed through targeting such nutrient dependency. Various nutrients including several amino acids and glucose have been found to induce dependency in genetic alteration- or context-dependent manners. In this review, we discuss the extensively studied nutrient dependency and the biological mechanisms behind such vulnerabilities. Besides, existing applications and strategies to target nutrient dependency in different cancer types, accompanied with remaining challenges to further exploit these metabolic vulnerabilities to improve cancer therapies, are reviewed.